2021
DOI: 10.1038/s41467-021-22876-9
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning model for identifying patients at risk for wild-type transthyretin amyloid cardiomyopathy

Abstract: Transthyretin amyloid cardiomyopathy, an often unrecognized cause of heart failure, is now treatable with a transthyretin stabilizer. It is therefore important to identify at-risk patients who can undergo targeted testing for earlier diagnosis and treatment, prior to the development of irreversible heart failure. Here we show that a random forest machine learning model can identify potential wild-type transthyretin amyloid cardiomyopathy using medical claims data. We derive a machine learning model in 1071 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 30 publications
6
90
2
Order By: Relevance
“…The study population was divided into a training set and a test set at a ratio of 80:20 using stratified random sampling 21 . To avoid AA methods overfitting the test set, we applied fivefold cross-validation to the training set in validating procedure, and the area under the receiver operating curve (AUC) was averaged over all the data fold sets 22 , 23 . The stratified cross-validation method ensures that each training and test fold has a similar distribution of outcomes with the entire dataset to reduce bias in the training and evaluating processes.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was divided into a training set and a test set at a ratio of 80:20 using stratified random sampling 21 . To avoid AA methods overfitting the test set, we applied fivefold cross-validation to the training set in validating procedure, and the area under the receiver operating curve (AUC) was averaged over all the data fold sets 22 , 23 . The stratified cross-validation method ensures that each training and test fold has a similar distribution of outcomes with the entire dataset to reduce bias in the training and evaluating processes.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic screening paradigms, including through imaging and automated medical record feature review, have shown the opportunity to identify patients with underdiagnosed diseases that are increasingly recognized as more prevalent than was previously thought. 5 , 6 , 7 , 8 , 9 The ability to reliably distinguish between cardiac disease types with similar morphologic features but different causes would also enhance specificity for linking genetic risk variants and determining mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The application of artificial intelligence for screening CA has been reported recently. 51,52 The authors showed that machine learning models well identified patients with CA.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…the adverse effects of these agents (hypotension, kidney failure, conduction disorders) overwhelm benefits. 52 The use of calcium antagonists, particularly non-dihydropyridine calcium channel blocker and digoxin is also avoided. 53 The 2 nd area of treatment is reserved for hematologists and concerns AL-CA.…”
Section: Therapeutic Proceduresmentioning
confidence: 99%